Life Satisfaction as a Predictor of Phubbing in College Students - Kristin Rahmani; Heliany Kiswantomo; Victoria Hannah Pali (Green Publisher Indonesia, 2025)
Phubbing, or phone snubbing, refers to the tendency of individuals to ignore people around them by focusing excessively on their mobile phones. This phenomenon is increasingly common among college students, who are among the highest users of the internet and smartphones in Indonesia. Previous research indicates that psychological factors, particularly life satisfaction, may influence phubbing behavior. The purpose of this study is to investigate whether life satisfaction can predict phubbing among college students. This research employed a quantitative approach with a causal–correlational design. A total of 200 students aged 18–25 years were recruited using a convenience sampling technique. Life satisfaction was measured with the Satisfaction with Life Scale (SWLS), while phubbing was assessed using the Phubbing Scale. Both instruments showed adequate levels of validity and reliability. Data were collected through online questionnaires and analyzed using simple linear regression after classical assumption tests were met. The results indicate that life satisfaction does not significantly predict phubbing behavior, either in overall phubbing scores or in its dimensions of communication disturbance and phone obsession. These findings suggest that life satisfaction alone cannot explain the occurrence of phubbing, and other psychological factors such as loneliness and flow may play a more critical role. In conclusion, life satisfaction is not a predictor of phubbing among Indonesian college students. Theoretically, this study contributes to the literature on digital behavior and positive psychology. Practically, the findings provide insights for educators, parents, and policymakers to design strategies that address phubbing behavior more effectively.